2019
DOI: 10.1136/jclinpath-2019-206056
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of peritoneal elastic laminal invasion improves survival stratification of pT3 and pT4a colorectal cancer: a meta-analysis

Abstract: Evaluating peritoneal elastic laminal invasion (ELI) has been proposed as an additional assessment for pT3 colorectal cancers (CRC). Its clinical significance has not yet been established. We performed a meta-analysis to investigate the prognostic impact of ELI assessment for subcategorisation of pT3 CRC. We performed a search in three electronic databases. HR and its 95% CI for overall survival (OS) and disease-free survival (DFS) were calculated using the random effects model weighted by the inverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Lu et al, proposed ELI assessed with elastic stain as prognostic factors for stage II colon cancer, and might be an indication to postoperative adjuvant chemotherapy [ 39 ]. Recently, a meta-analysis including six studies, recommended the sub-categorization of pT3 CRC by ELI for better prognostic assessment and treatment strategy of patients with CRC [ 40 ]. Our analysis failed to confirm any significant impact of ELI on oncological outcome, and ELI as predictive factor at univariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al, proposed ELI assessed with elastic stain as prognostic factors for stage II colon cancer, and might be an indication to postoperative adjuvant chemotherapy [ 39 ]. Recently, a meta-analysis including six studies, recommended the sub-categorization of pT3 CRC by ELI for better prognostic assessment and treatment strategy of patients with CRC [ 40 ]. Our analysis failed to confirm any significant impact of ELI on oncological outcome, and ELI as predictive factor at univariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, excessive sample collection and staining will cause unnecessary waste. Therefore, it may be bene cial to choose patients with T3 stage tumours with peritoneal invasion for elastic lamina staining [15]. The elastic lamina has been found to move from the nontumour area of the peritoneum to the muscularis propria when the tumour invades normal tissues [11].…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer, the subserosal elastic lamina is located above the peritoneum [11]. Whether tumours have invaded tissues near the serosa can be evaluated by elastic lamina staining; such invasion is associated with worse prognoses among colon cancer patients [11][12][13][14][15]. Therefore, it has been suggested that CRC patients with ELI positive (ELI+) pT3 tumours and those with pT4a tumours should receive the same treatment [16].…”
Section: Introductionmentioning
confidence: 99%
“…1 Distinguishing pT4a from pT3 tumor (invading pericolonic fat tissue) is crucial as each command different therapeutic strategies. 6 Accurate assessment of serosal invasion is often challenging in routine clinical practice and clinical studies showed significant variabilities in reporting pT4a versus pT3 colon cancers 7 in all practice settings (academic vs private and subspecialty vs general signing out). 8 One challenge is that peritoneal clefts are often ignored/ missed, though careful sampling of these areas has been shown to enhance detection of serosal involvement.…”
Section: Discussionmentioning
confidence: 99%